Adolescents' perceptions of social risk and prosocial tendencies: Developmental change and individual differences. Issue 1 (1st September 2022) - Armstrong‐Carter, Emma; Do, Kathy T.; Duell, Natasha; Kwon, Seh‐Joo; Lindquist, Kristen A.; Prinstein, Mitch J.; Telzer, Eva H.
Abstract: Many prosocial behaviors involve social risks such as speaking out against a popular opinion, bias, group norm, or authority. However, little is known about whether adolescents' prosocial tendencies develop over time with their perceptions of social risks. This accelerated longitudinal study used within‐subject growth‐curve analyses to test the link between adolescents' prosocial tendencies and social risk perceptions. Adolescents completed self‐reports annually for 3 years ( N = 893; M age = 12.30 years, 10–14 years at Wave 1, and 10–17 years across the full study period; 50% girls, 33% White non‐Latinx, 27% Latinx, 20% African American, 20% mixed/other race). The association between social risk tolerance and prosocial tendencies changed significantly across adolescence. Specifically, for younger adolescents, more prosocial tendencies were associated significantly with less social risk tolerance, whereas for relatively older adolescents, more prosocial tendencies were associated marginally with more social risk tolerance. Additional individual differences by empathy (but not sensation seeking) emerged. These findings suggest that prosocial tendencies across adolescence may be associated with an underlying ability to tolerate social risks.